Cephalopoda as prey of juvenile Southern elephant seals at Isla 25 de Mayo/King George, South Shetland Islands - Burdman,Luciana (2015)
The aim of the present study was to enhance the knowledge of the feeding habits of the juvenile component of the population of Southern elephant seals [Mirounga leonina (Linnaeus, 1758)] from Isla 25 de Mayo, South Shetland Islands, age class whose diet information is scarce. A total of 60 individuals were stomach lavaged in the spring - summer seasons of three consecutive years (2003, 2004 and 2005) of which 53.3 % (n = 32) presented food remnants. The Antarctic glacial squid Psychroteuthis glacialis Thiele, 1921 was the dominant prey taxon in terms of frequency of occurrence (68.7%), numerical abundance (60.1%) and biomass (51.5%), contributing 84.1% to the total relative importance index. Other squid prey species of importance were Slosarczykovia circumantartica Lipinski, 2001 in terms of occurrence (37.5%) and numerical abundance (14%) and Moroteuthis knipovitchi Filippova, 1972 in terms of biomass (16%). All identified cephalopod prey taxa are distributed south of the Antarctic Polar Front, except for the squid Martialia hyadesi Rochebrune & Mabille, 1889 which has a circumpolar distribution associated to the Polar Frontal Zone. No significant differences in the sizes of P. glacialis preyed upon by elephant seals were found between sexes and years. However, significant interannual differences were found in the taxonomical composition of their diet. This would be associated with temporal changes in food availability at the foraging areas of seals, which in turn may have been influenced by changes in oceanographic conditions as a result of the El Niño Southern Oscillation (ENSO) phenomenon that occurred during part of the study period. Furthermore, a differential response of males and females to this temporal variation was observed, with the former being also associated to a predation on octopods. This would suggest a sexual segregation in foraging habits of this species from the early stages of its life cycle.